Lecture Notes in Computer Science
DOI: 10.1007/978-3-540-71783-6_23
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Evolutionary Algorithms and Differential Evolution for the Online Optimization of Fermentation Processes

Abstract: Abstract. Although important contributions have been made in recent years within the field of bioprocess model development and validation, in many cases the utility of even relatively good models for process optimization with current state-of-the-art algorithms (mostly offline approaches) is quite low. The main cause for this is that open-loop fermentations do not compensate for the differences observed between model predictions and real variables, whose consequences can lead to quite undesirable consequences.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…This could be explained for the simplicity of the microbial growth model, which does not account for deleterious effects such as overflow metabolism or inhibitory shocks for substrate feeding. It is worthwhile to mention that the obtained results, in terms of GA and DE comparison, corroborates with the empirically observed in the literature, as the genetic algorithm exhibits in general more result variability than the differential evolution [50,62]. Also, it is important to notice that for both algorithms the exponential parametrization of the feed rate exhibited larger variaton among the results (expressed in terms of its standard deviation), especially for the assays with higher time interval between the optimization studies.…”
Section: Effect Of the Interval Between Optimization Cycles And Paramsupporting
confidence: 88%
See 2 more Smart Citations
“…This could be explained for the simplicity of the microbial growth model, which does not account for deleterious effects such as overflow metabolism or inhibitory shocks for substrate feeding. It is worthwhile to mention that the obtained results, in terms of GA and DE comparison, corroborates with the empirically observed in the literature, as the genetic algorithm exhibits in general more result variability than the differential evolution [50,62]. Also, it is important to notice that for both algorithms the exponential parametrization of the feed rate exhibited larger variaton among the results (expressed in terms of its standard deviation), especially for the assays with higher time interval between the optimization studies.…”
Section: Effect Of the Interval Between Optimization Cycles And Paramsupporting
confidence: 88%
“…The GA and the DE represent two important members of the evolutionary computation techniques, which are referred to for their good performance on optimization problems applied to biotechnology [18,50]. The generic form of the GA and DE methods algorithms are schematically outlined in Figures 1 and 2, respectively.…”
Section: Dynamic Optimization Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the dynamic optimization of the fermentation processes is a problem requiring not only powerful algorithms but also carefully chosen methodologies, Rocha et al (2007) proposed an online optimization procedure based on DE. Three different case studies were considered: (1) fed-batch recombinant Escherichia coli fermentation, where microorganisms follow three different metabolic paths (oxidative growth on glucose, fermentative growth on glucose, and oxidative growth on acetic acid); (2) a hybridoma reactor; and (3) fed-batch bioreactor for the production of ethanol by Saccharomyces cerevisiae.…”
Section: Simple De Versions Used In Process Optimizationmentioning
confidence: 99%
“…However, when noisier settings were employed, the DE algorithm performance decreased. Using the same case studies and objectives (from Rocha et al 2007), Mendes et al (2008) performed online and offline optimizations of input variables by applying three distinct algorithms, namely DE, a real value EA, and a fully informed particle swarm (FIPS). The results obtained for the offline optimization indicated that DE/Rand/1/ bin has the best results, followed closely by DE/best/2/ bin and FIPS.…”
Section: Simple De Versions Used In Process Optimizationmentioning
confidence: 99%